Pengaruh Pelatihan Dan Budaya Kaizen Terhadap Kinerja Karyawan Di PT. Bank Central Asia, Tbk. Cabang Kelapa Gading Raya - Evelyn Caluela; Sumbogo, Ignatius Ario (STREAMING, 2024)
This study aims to determine the effect of training and kaizen culture on employee performance at PT Bank Central Asia, Tbk Kelapa Gading Raya Branch. Field research methods with a type of quantitative approach. The employee population is 45 people and the sample taken is 45 people using the Non Probability Sampling technique. Data processing uses multiple linear regression using SPSS Version 25 software. The results of this study conclude that there is a significant influence between training on employee performance and kaizen culture on employee performance and simultaneously have a positive influence on employee performance.